Phase separation in innate immune response and inflammation-related diseases - Ma, Huihui; Liu, Mingxi; Fu, Rao; Feng, Jia; Ren, Haoran; Cao, Jingyan; Shi, Ming (Frontiers in Immunology, 2023)
Inflammation induced by nonspecific pathogenic or endogenous danger signals is an essential mechanism of innate immune response. The innate immune responses are rapidly triggered by conserved germline-encoded receptors that recognize broad patterns indicative of danger, with subsequent signal amplification by modular effectors, which have been the subject of intense investigation for many years. Until recently, however, the critical role of intrinsic disorder-driven phase separation in facilitating innate immune responses went largely unappreciated. In this review, we discuss emerging evidences that many innate immune receptors, effectors, and/or interactors function as “all-or-nothing” switch-like hubs to stimulate acute and chronic inflammation. By concentrating or relegating modular signaling components to phase-separated compartments, cells construct flexible and spatiotemporal distributions of key signaling events to ensure rapid and effective immune responses to a myriad of potentially harmful stimuli.